Vol.2 (History of diplomacy) - Jonsson, Christer (ed.); Langhorne, Richard (ed.) (London, 2004)
This three volume set includes seminal journal articles and book excerpts dealing with various aspects of diplomacy. Volume I deals with the theory of diplomacy, Volume II with the history of diplomacy, and Volume III with problems and issues in contemporary diplomacy. Forty years ago, Lord Strang, a former British diplomat, remarked: 'In a world where war is everybody's tragedy and everybody's nightmare, diplomacy is everybody's business'. His words are equally, if not more, valid and pertinent today. And in recent years the academic study of diplomacy appears to have been revitalized. Specialized research centres in Europe and the United States have encouraged new projects and launched publication series. Concomitantly, courses on diplomacy appear ever more in the curricula of universities worldwide. With growing interest in diplomacy, earlier writings on the topic are coming in demand as well. This set of volumes is designed to meet that demand, at the same time as it draws on contemporary scholarship.
Keywords: Diplomacy - foreign relations